EL-BAIT”: (Ecotheology-Based Innovative Technopreneurship): A Conceptual Model Bridging Innovation, Digital Ethics, and Response to Climate Crisis” - Ahmad Sirajuddin; N.W. Islami Rahayu; Ubaidillah (ABM: International Journal of Administration, Business and Management, 2025)
The increasing pressure for technological innovation in the digital economy has triggered a crisis of values, where technopreneurial practices often neglect ethical, ecological, and spiritual dimensions. This phenomenon highlights a critical gap in current digital business models, which rarely integrate faith-based principles and sustainability frameworks. Drawing from the theories of Triple Bottom Line, Stakeholder Theory, TOE Framework, The House model, and Maqosidus shariah principles, this study proposes a conceptual model called EL-BAIT (Ecotheology-Based Innovative Technopreneurship) that integrates technological innovation, faith commitment, and ecological ethics. The model addresses the urgent need for a holistic entrepreneurial paradigm that fosters both economic competitiveness and socio-environmental legitimacy. This article employs a critical literature review method by synthesizing empirical studies and conceptual frameworks published between 2010–2025 from Scopus-indexed journals and DOAJ. Key variables were clustered thematically and mapped into an integrated conceptual diagram of Eco-theological innovative technopreneurship. The findings reveal three components – Technological innovation, Faith-driven entrepreneurship, and sustainability as the strategic key way of ethical green technology innovation and five core components—faith-led leadership, digital capability, stakeholder empathy, green organizational culture, and sustainability awareness —as the supporting behavior. A real life case study will be used to illustrate the proposed model. This model serves as a normative guide for ethical startup development in Muslim-majority and sustainability-driven societies. Future research is recommended to empirically validate the ELBAIT model through case studies or participatory design involving digital entrepreneurs, policymakers, and faith-based communities.